Orange/yellow InGaN/AlN nanodisk light emitting diodes. Issue 11 (24th October 2013) - Mathew, Manish; Sodabanalu, Hassanet; Sugiyama, Masakazu; Nakano, Yoshiaki; Yamaguchi, Hiroshi; Kumakura, Kazuhide
Abstract Indium gallium nitride (InGaN)/aluminium nitride (AlN) self‐assembled nanodisk light emitting diode (LED) structures were grown on sapphire substrate using metalorganic vapor phase epitaxy (MOVPE). Structural analysis shows that the initial AlN layer plays a crucial role in the formation of nanodisk structure. Nanodisks were formed due to cracks introduced in the first AlN layer on n‐GaN template. The succeeding InGaN/AlN layers introduced branching of the nanodisks due to cracks from the initial AlN layer. The structural properties of nanodisk were confirmed from atomic force microscopy (AFM) and high‐angle annular dark‐field (HAADF) images. Observation of electroluminescence (EL) showed that, at lower injection current orange (605 nm) color light was emitted and that when the injection current increased the wavelength shifted from orange to yellow (586 nm). This large EL blue shift observed in the nanodisk LED was due weakening of the quantum confined stark effect (QCSE) at high injection current. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)